2018
DOI: 10.1177/0192636518802033
|View full text |Cite
|
Sign up to set email alerts
|

What Are Principals’ Perceptions? Recommendations for Improving the Supervision and Evaluation of Principals

Abstract: The goals for this qualitative study were to examine principals’ perceptions regarding their own supervision and evaluation. Two research questions guided the qualitative inquiry: (1) What are the greatest strengths of your own supervision and evaluation? and (2) What recommendations would you give to superintendents to improve your own supervision and evaluation? The study used an online tool to gather perceptions from principals regarding their own evaluation and supervision. Participants solicited included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In cases where policymakers do point to research, we wonder if they are using such findings in appropriate ways to inform policy (Lubienski et al, 2016). In alignment with extant literature (Hvidston et al, 2015(Hvidston et al, , 2018McMahon et al, 2014), we also wonder: How were superintendents trained to evaluate principals and what was the rigor of such trainings (e.g., required a passing score on a test, multiple trainings throughout the year, interrater reliability establishment and attention to coder drift)? How prepared are superintendents to evaluate principals?…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In cases where policymakers do point to research, we wonder if they are using such findings in appropriate ways to inform policy (Lubienski et al, 2016). In alignment with extant literature (Hvidston et al, 2015(Hvidston et al, , 2018McMahon et al, 2014), we also wonder: How were superintendents trained to evaluate principals and what was the rigor of such trainings (e.g., required a passing score on a test, multiple trainings throughout the year, interrater reliability establishment and attention to coder drift)? How prepared are superintendents to evaluate principals?…”
Section: Discussionmentioning
confidence: 75%
“…However, research shows principals desire honest and open communication in relation to their evaluations from supervisors in the form of positive reinforcement and constructive criticism on areas for improvement (Hvidston et al, 2018). This study concluded such reinforcement and criticism requires that the superintendent is "prepared and knowledgeable" (p. 220).…”
Section: Trained Supervisorsmentioning
confidence: 82%
See 1 more Smart Citation
“…One potential rationale for the difference between the significant perceptions regarding supervision could be that not all instructional supervisors "made intentional moves to help principals value their own development as instructional leaders rather than to engage in instructional leadership work such as classroom observations as a matter of compliance" (Honig, 2012, p. 747). It is possible some superintendents might have difficulty creating this value in supervision with the past practice of supervision of principals emphasizing checklists or compliance (McMahon, Peters, & Schumacher, 2014) without developing trust or communication between principal and superintendent (Hvidston, McKim, & Holmes, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…At this meeting, they determined the goals, targets to be achieved and created a team of assistant principals to implement academic supervision. The implementation of supervision could be more directed and effective if it refers to the planning made professionally (Honig & Rainey, 2019;Hvidston et al, 2018;Noor et al, 2020). Next, the principal held a meeting with the teachers to socialise the academic supervision programme.…”
Section: Planningmentioning
confidence: 99%